GEOLOGY OF BUAHDUA AREA, SUMEDANG DISTRICT, WEST JAVA PROVINCE - Raditya Rendra, Pradnya Paramarta; Sulaksana, Nana (Journal of Geological Sciences and Applied Geology, 2019)
Buahdua area is located in Sumedang District, West Java Province with coordinate 107°53’52,30” E - 107°59’18,83” E and 6°44’2,15” S - 6°38’38,39” S.  This research aims to identify and characterize the geology of Buahdua area and its surrounding. This research used field observation, studio, and laboratory analysis method. Digital maps used to carried out processing step in studio and field tools such as geological hammer, camera, GPS, and compass used to carried out field observation. Rock samples are taken for laboratory analysis. Based on field observation, studio, and laboratory analysis, the research area can be divided into four morphology unit namely very gentle sloping hill, gentle sloping hill, rather steep hill, and steep hill morphology unit. Also, the research area has four drainage patterns namely anastomotic, subdendritic, subparalel, and subrectangular drainage pattern. The lithostratigraphic units in the research are can be divided into three units namely claystone (Tmbl), sandstone (Tmbpl), and volcanic breccia (Kbv) unit, and alluvium (Kal). The geological structures developed in the research area are shear joint and oblique fault (Cikandung and Kamal oblique fault). Geological history of the research area was started from middle Miocene (N9) when claystone unit was deposited in deep marine environment. In middle Miocene (N9 - N10), sandstone unit was deposited in deep marine environment. After those rock unit, there was tectonic activity in Pliocene - Plistocene caused geological structures, shear joint and oblique fault. Occurences volcanic activity after tectonic activity caused volcanic breccia unit was deposited. After those process, alluvium was deposited in Cikandung River until now.